PENGARUH TEKNIK QUESTION STUDENT HAVE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 26 BANDAR LAMPUNG TAHUN PELAJARAN 2016/2017 - Astuti, Yuli (LPPM STKIP PGRI Bandar Lampung, 2019)
The author in this study uses the experimental method, and data analysis uses statistical formulas. The population in this study were all class VIII semester even SMPN 26 Bandar Lampung consisting of 2 classes with a total of 242 students, while the sample was taken 2 classes namely class VIII.1 as the experimental class, and class VIII.2 as the control class. Samples were taken using simple Question Student Have techniques. To find out the mathematical communication skills students are given a test in the form of essays of 5 questions which have been tested for validity and reliability first. From the results of hypothesis testing using the t-hit statistical formula, the value t = 7.55 is obtained. From the distribution table t at a significant level of 5% it is known that t=t (1-Î±) = 2.00 thit>tdaf so it can be concluded that